2009
DOI: 10.1007/s12094-009-0387-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life two years after radical prostatectomy, prostate brachytherapy or external beam radiotherapy for clinically localised prostate cancer: the Catalan Institute of Oncology/Bellvitge Hospital experience

Abstract: Quality of life 2 years after treatment for prostate cancer shows wide variability. Radical prostatectomy had the largest negative impact on the sexual and urinary incontinence domains. Differences between external radiation and brachytherapy were relatively small. Brachytherapy led to a moderate increase in urinary irritation compared to the other 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…22,33,46 In an RCT in low-risk patients, results were consistent with the above observational studies at 1 year, but these differences for PROs were not sustained at 5 years.…”
Section: 46supporting
confidence: 64%
“…22,33,46 In an RCT in low-risk patients, results were consistent with the above observational studies at 1 year, but these differences for PROs were not sustained at 5 years.…”
Section: 46supporting
confidence: 64%
“…Acutely after prostatectomy, 80% to 90% of patients report difficulty with erections (9,10), but this proportion decreases to approximately 60% by 2 years (9,19,21). After radiation, erectile dysfunction increases with time and is reported by 50% to 60% of external beam radiation patients and 20% to 50% of brachytherapy patients at 2 years (9,10,13,19,22). Those who received radiation alone (without androgen deprivation therapy) had better outcomes (9).…”
Section: Brief Communicationmentioning
confidence: 99%
“…Many recent studies have examined quality of life following treatment and have shown that the choice of treatment has a considerable impact (Table 4). [70][71][72][73][74][75] A controlled study examined the negative effects three years after treatment for localized prostate cancer and reported worse urinary function associated with surgery; whereas bowel function was poorest with radiotherapy. 70 Sexual dysfunction was similar between groups.…”
Section: Comparative Health-related Quality Of Life Estimates Followimentioning
confidence: 99%
“…One study examined the QOL after radical prostatectomy, radiotherapy or brachytherapy and demonstrated QOL varies as a function of treatment. 71 A general health-related QOL questionnaire was used (Medical Outcomes Study Short-Form 36 ), composed of physical (PCS) and mental (MCS) component scores, and a specific health-related quality of life (HRQOL) questionnaire with domains of urinary, sexual and incontinence. At 2 years these three QOL measures were worse with prostatectomy.…”
Section: Comparative Health-related Quality Of Life Estimates Followimentioning
confidence: 99%